Do Lower Minimum Wages for Young Workers Raise Their Employment? Evidence from a Danish Discontinuity - Kreiner, Claus Thustrup; Reck, Daniel; Skov, Peer Ebbesen (The Review of Economics and Statistics, 2020)
We estimate the impact of youth minimum wages on youth employment by exploiting a large discontinuity in Danish minimum wage rules at age 18, using monthly payroll records for the Danish population. The hourly wage jumps by 40% at the discontinuity. Employment falls by 33%, and total input of hours decreases by 45%, leaving the aggregate wage payment almost unchanged. We show theoretically how the discontinuity may be exploited to evaluate policy changes. The relevant elasticity for evaluating the effect on youth employment of changes in their minimum wage is in the range 0.6 to 1.1.